Khazanah Warisan Tempatan di Perpustakaan Hamzah Sendut, Universiti Sains Malaysia: Koleksi Kaum Peranakan Asia Tenggara - Saad, Siti Roudhah Mohamad; Mohamad, Radia Banu Jan; Jaafar, Cik Ramlah Che; Misaridin, Shahriza Fadly (Persatuan Pustakawan Malaysia, 2011)
This paper will describe the process of collection development of Southeast Asia Peranakans in Malaysiana and Archives Division, Hamzah Sendut Library, Universiti Sains Malaysia. As a central repository of knowledge and information, the Library plays an important role in ensuring the preservation of materials which have traditional and local knowledge values. Collection development is a main activity in a library, therefore, the purpose and significance are also described in this paper. The collection development on South East Asia Peranakan involves the collection, storage, preservation and dissemination of information relating to the Peranakan people in Southeast Asia, particularly Chinese Peranakan, Jawi Peranakan, Peranakan Indians (The Chetti) and The Siam Peranakan (Malay Sam Sam). Initiatives that have been taken to realize the collection development of the Southeast Asia Peranakan will be described and explained in detail. In addition, the challenges and obstacles faced during the development process of this collection will also be clarified. This collection will give a specific disclosure of the existence of the Peranakan people, help track and preserve traditional heritage treasures so as not to be diminished by the passage of time. This collection can also be used as a reference to assist the teaching, learning and research of future generations. This effort could also be benchmarked for the development of special collection